Convergence of rotational hardening with bounds in clay plasticity. Issue 1 (21st October 2019) - Dafalias, Y. F.; Taiebat, M.; Rollo, F.; Amorosi, A.
Abstract : Convergence of the rotational hardening variable α used in the anisotropic models of clay plasticity, with a constitutively defined attractor/bound α b ( η ), function of the stress ratio η, under fixed η loading, is analytically investigated. It is analytically shown that depending on various parameters of the rate equation of the evolution of α, such convergence may or may not occur despite the apparent necessity of convergence stemming from the form of the evolution equation of α .